The effect of early engineering education with illustrated children's books on geometry and spatial perception skills - Erol, Mustafa; Erol, Ahmet; Erol, Merve Canbeldek (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2025)
In this study, we investigated the effects of early engineering education (EEE) practices on 6 year-old children's geometry and spatial perception (GSP) skills. We structured the study within the framework of a quasi-experimental design with pre-test, post-test, and control groups. The study group comprises 32 6 year-old children studying in a city northwest of T & uuml;rkiye; 17 children were in the control group and 15 in the experimental group. The average age of children was 69 months. Children in the experimental group participated in an eight-week engineering training with illustrated children's books (ICBs). The study's data were collected through a geometry and spatial perception test (GSP-T). The GSP-T scores of the experimental group of children who participated in the ICB-based EEE showed a positive change compared to the control group. Our findings show that ICB and engineering integration in early childhood classrooms can support typically developing children's skills in geometry and spatial perception.
Keywords: Early childhood; early engineering education; early STEM education; early geometry skills; Education & Educational Research